A nonenzymatic reduced graphene oxide-based nanosensor for parathion - Sarani Sen; Anurag Roy; Ambarish Sanyal; Parukuttyamma Sujatha Devi (Beilstein Journal of Nanotechnology, 2022)
Organophosphate-based pesticides (e.g., parathion (PT)) have toxic effects on human health through their residues. Therefore, cost-effective and rapid detection strategies need to be developed to ensure the consuming food is free of any organophosphate-residue. This work proposed the fabrication of a robust, nonenzymatic electrochemical-sensing electrode modified with electrochemically reduced graphene oxide (ERGO) to detect PT residues in environmental samples (e.g., soil, water) as well as in vegetables and cereals. The ERGO sensor shows a significantly affected electrocatalytic reduction peak at −0.58 V (vs Ag/AgCl) for rapid quantification of PT due to the amplified electroactive surface area of the modified electrode. At optimized experimental conditions, square-wave voltammetric analysis exhibits higher sensitivity (50.5 μA·μM−1·cm−2), excellent selectivity, excellent stability (≈180 days), good reproducibility, and repeatability for interference-free detection of PT residues in actual samples. This electrochemical nanosensor is suitable for point-of-care detection of PT in a wide dynamic range of 3 × 10−11–11 × 10−6 M with a lower detection limit of 10.9 pM. The performance of the nanosensor was validated by adding PT to natural samples and comparing the data via absorption spectroscopy. PT detection results encourage the design of easy-to-use nanosensor-based analytical tools for rapidly monitoring other environmental samples.